67.3k views
3 votes
Please solve with explanation

Please solve with explanation-example-1
User Olleicua
by
6.4k points

1 Answer

3 votes

Answer:

3
(9)/(10)

Explanation:

Note that + (- ) = -

Given

6
(1)/(5) + ( - 2
(3)/(10))

= 6
(1)/(5) - 2
(3)/(10)

Change both mixed numbers into improper fractions, that is

=
(31)/(5) -
(23)/(10)

We require both denominators to be common before subtracting.

Multiply the numerator/ denominator of the first fraction by 2

=
(31(2))/(5(2)) -
(23)/(10)

=
(62)/(10) -
(23)/(10)

Now subtract numerators leaving the denominator

=
(62-23)/(10)

=
(39)/(10) ← change back to a mixed number

= 3
(9)/(10)